# The-sums-of-the-first-n-terms-of-two-AP-s-are-in-the-ratio-3n-31-5n-3-Show-that-their-9-th-terms-are-equal-

Question Number 2619 by Rasheed Soomro last updated on 23/Nov/15
$${The}\:{sums}\:{of}\:{the}\:{first}\:\:{n}\:\:\:{terms}\:{of}\:{two}\:{AP}\:'{s}\:{are} \\$$$${in}\:{the}\:{ratio}\:\:\mathrm{3}{n}+\mathrm{31}\::\:\:\mathrm{5}{n}−\mathrm{3}\:.\:{Show}\:{that}\:{their}\:\mathrm{9}^{{th}} \:{terms} \\$$$${are}\:{equal}. \\$$
Commented by Yozzi last updated on 24/Nov/15
$${S}_{\mathrm{1}} \left({n}\right)=\frac{{n}}{\mathrm{2}}\left({a}_{\mathrm{1}} +{l}_{\mathrm{1}} \right)=\frac{{nc}_{\mathrm{1}} }{\mathrm{2}},\:{S}_{\mathrm{2}} \left({n}\right)=\frac{{n}}{\mathrm{2}}\left({a}_{\mathrm{2}} +{l}_{\mathrm{2}} \right)=\frac{{nc}_{\mathrm{2}} }{\mathrm{2}} \\$$$$\frac{{S}_{\mathrm{1}} \left({n}\right)}{{S}_{\mathrm{2}} \left({n}\right)}=\frac{\mathrm{3}{n}+\mathrm{31}}{\mathrm{5}{n}−\mathrm{3}}=\frac{{c}_{\mathrm{1}} }{{c}_{\mathrm{2}} }. \\$$$$\mathrm{3}{c}_{\mathrm{2}} {n}+\mathrm{31}{c}_{\mathrm{2}} =\mathrm{5}{c}_{\mathrm{1}} {n}−\mathrm{3}{c}_{\mathrm{1}} \\$$$${n}\left(\mathrm{3}{c}_{\mathrm{2}} −\mathrm{5}{c}_{\mathrm{1}} \right)=−\mathrm{3}{c}_{\mathrm{1}} −\mathrm{31}{c}_{\mathrm{2}} \\$$$${n}=\frac{\mathrm{3}{c}_{\mathrm{1}} +\mathrm{31}{c}_{\mathrm{2}} }{\mathrm{5}{c}_{\mathrm{1}} −\mathrm{3}{c}_{\mathrm{2}} } \\$$$${n}−\mathrm{1}=\frac{\mathrm{34}{c}_{\mathrm{2}} −\mathrm{2}{c}_{\mathrm{1}} }{\mathrm{5}{c}_{\mathrm{1}} −\mathrm{3}{c}_{\mathrm{2}} } \\$$$$\Delta={T}_{\mathrm{1}} \left(\mathrm{9}\right)−{T}_{\mathrm{2}} \left(\mathrm{9}\right)={a}_{\mathrm{1}} −{a}_{\mathrm{2}} +\mathrm{8}\left({d}_{\mathrm{1}} −{d}_{\mathrm{2}} \right) \\$$$${l}_{\mathrm{1}} ={a}_{\mathrm{1}} +\left({n}−\mathrm{1}\right){d}_{\mathrm{1}} \Rightarrow{d}_{\mathrm{1}} =\frac{{l}_{\mathrm{1}} −{a}_{\mathrm{1}} }{{n}−\mathrm{1}} \\$$$$\delta={d}_{\mathrm{1}} −{d}_{\mathrm{2}} =\frac{{l}_{\mathrm{1}} −{a}_{\mathrm{1}} −{l}_{\mathrm{2}} +{a}_{\mathrm{2}} }{{n}−\mathrm{1}} \\$$$$\delta=\frac{\left({l}_{\mathrm{1}} +{a}_{\mathrm{2}} −{a}_{\mathrm{1}} −{l}_{\mathrm{2}} \right)\left(\mathrm{5}{c}_{\mathrm{1}} −\mathrm{3}{c}_{\mathrm{2}} \right)}{\mathrm{34}{c}_{\mathrm{2}} −\mathrm{2}{c}_{\mathrm{1}} } \\$$$$\\$$$$\\$$
Answered by prakash jain last updated on 24/Nov/15
$$\mathrm{Let}\:\:\mathrm{2}{a}_{\mathrm{1}} +\left({n}−\mathrm{1}\right){d}_{\mathrm{1}} =\left(\mathrm{3}{n}+\mathrm{31}\right){k}_{\mathrm{1}} ,\:\mathrm{then} \\$$$$\mathrm{2}{a}_{\mathrm{2}} +\left({n}−\mathrm{1}\right){d}_{\mathrm{2}} =\left(\mathrm{5}{n}−\mathrm{3}\right){k}_{\mathrm{1}} \\$$$$\left(\mathrm{2}{a}_{\mathrm{1}} −{d}_{\mathrm{1}} \right)+{nd}_{\mathrm{1}} =\mathrm{3}{nk}_{\mathrm{1}} +\mathrm{31}{k}_{\mathrm{1}} \:\:\:\:…\left(\mathrm{1}\right) \\$$$$\mathrm{If}\:\left(\mathrm{1}\right)\:\mathrm{is}\:\mathrm{true}\:\mathrm{for}\:\mathrm{all}\:{n}\:\left({coeffiient}\:{must}\:{be}\:{equal}\right) \\$$$${nd}_{\mathrm{1}} =\mathrm{3}{nk}_{\mathrm{1}} \Rightarrow{d}_{\mathrm{1}} =\mathrm{3}{k}_{\mathrm{1}} \\$$$$\mathrm{2}{a}_{\mathrm{1}} −{d}_{\mathrm{1}} =\mathrm{31}{k}_{\mathrm{1}} \Rightarrow{a}_{\mathrm{1}} =\mathrm{17}{k}_{\mathrm{1}} \\$$$$\mathrm{similarly} \\$$$${d}_{\mathrm{2}} =\mathrm{5}{k}_{\mathrm{1}} \\$$$${a}_{\mathrm{2}} ={k}_{\mathrm{1}} \\$$$$\mathrm{9}{th}\:\mathrm{term} \\$$$${a}_{\mathrm{1}} +\mathrm{8}{d}_{\mathrm{1}} =\mathrm{17}{k}_{\mathrm{1}} +\mathrm{24}{k}_{\mathrm{1}} =\mathrm{41}{k}_{\mathrm{1}} \\$$$${a}_{\mathrm{2}} +\mathrm{8}{d}_{\mathrm{2}} ={k}_{\mathrm{1}} +\mathrm{40}{k}_{\mathrm{1}} =\mathrm{41}{k}_{\mathrm{1}} \\$$$$\mathrm{So}\:\mathrm{9}{th}\:\mathrm{terms}\:\mathrm{are}\:\mathrm{equal}. \\$$
Answered by Rasheed Soomro last updated on 24/Nov/15
$${Without}\:{repeating}\:{understood}\:{things} \\$$$$\frac{\frac{{n}}{\mathrm{2}}\left[\mathrm{2}{a}_{\mathrm{1}} +\left({n}−\mathrm{1}\right){d}_{\mathrm{1}} \right]}{\frac{{n}}{\mathrm{2}}\left[\mathrm{2}{a}_{\mathrm{2}} +\left({n}−\mathrm{1}\right){d}_{\mathrm{2}} \right]}=\frac{\mathrm{3}{n}+\mathrm{31}}{\mathrm{5}{n}−\mathrm{3}}\:\:\:\:\left[{Given}\right] \\$$$${a}_{\mathrm{1}} +\mathrm{8}{d}_{\mathrm{1}\:} \left({T}_{\mathrm{9}} \right)={a}_{\mathrm{2}} +\mathrm{8}{d}_{\mathrm{2}} \left({t}_{\mathrm{9}} \right)\:\:\:\:\:\:\:\:\:\left[{Required}\right]\:\:\:\: \\$$$$\frac{\frac{{n}}{\mathrm{2}}\left[\mathrm{2}{a}_{\mathrm{1}} +\left({n}−\mathrm{1}\right){d}_{\mathrm{1}} \right]}{\frac{{n}}{\mathrm{2}}\left[\mathrm{2}{a}_{\mathrm{2}} +\left({n}−\mathrm{1}\right){d}_{\mathrm{2}} \right]}=\frac{\mathrm{3}{n}+\mathrm{31}}{\mathrm{5}{n}−\mathrm{3}} \\$$$$\mathcal{O}{ur}\:{goal}:\:{To}\:{achieve}\:{a}_{\mathrm{1}} +\mathrm{8}{d}_{\mathrm{1}\:} {in}\:{numerator} \\$$$${and}\:{a}_{\mathrm{2}} +\mathrm{8}{d}_{\mathrm{2}} \:{in}\:{denominator}\:{because}\:{we}\:{want} \\$$$${to}\:{determine}\:{relation}\:{between}\:{T}_{\mathrm{9}} \:{and}\:{t}_{\mathrm{9}} \:. \\$$$$\Rightarrow\frac{\mathrm{2}{a}_{\mathrm{1}} +\left({n}−\mathrm{1}\right){d}_{\mathrm{1}} }{\mathrm{2}{a}_{\mathrm{2}} +\left({n}−\mathrm{1}\right){d}_{\mathrm{2}} }=\frac{\mathrm{3}{n}+\mathrm{31}}{\mathrm{5}{n}−\mathrm{3}} \\$$$$\Rightarrow\frac{\mathrm{2}\left[{a}_{\mathrm{1}} +\left(\frac{{n}−\mathrm{1}}{\mathrm{2}}\right){d}_{\mathrm{1}} \right]}{\mathrm{2}\left[{a}_{\mathrm{2}} +\left(\frac{{n}−\mathrm{1}}{\mathrm{2}}\right){d}_{\mathrm{2}} \right]}=\frac{\mathrm{3}{n}+\mathrm{31}}{\mathrm{5}{n}−\mathrm{3}} \\$$$$\Rightarrow\frac{{a}_{\mathrm{1}} +\left(\frac{{n}−\mathrm{1}}{\mathrm{2}}\right){d}_{\mathrm{1}} }{{a}_{\mathrm{2}} +\left(\frac{{n}−\mathrm{1}}{\mathrm{2}}\right){d}_{\mathrm{2}} }=\frac{\mathrm{3}{n}+\mathrm{31}}{\mathrm{5}{n}−\mathrm{3}} \\$$$${We}\:{want}\:\mathrm{8}\:{in}\:{place}\:{of}\:\frac{{n}−\mathrm{1}}{\mathrm{2}} \\$$$$\therefore\:\:\frac{{n}−\mathrm{1}}{\mathrm{2}}=\mathrm{8}\Rightarrow{n}=\mathrm{17} \\$$$$\Rightarrow\frac{{a}_{\mathrm{1}} +\mathrm{8}{d}_{\mathrm{1}} }{{a}_{\mathrm{2}} +\mathrm{8}{d}_{\mathrm{2}} }=\frac{\mathrm{3}\left(\mathrm{17}\right)+\mathrm{31}}{\mathrm{5}\left(\mathrm{17}\right)−\mathrm{3}}=\frac{\mathrm{82}}{\mathrm{82}}=\mathrm{1} \\$$$$\therefore\:{T}_{\mathrm{9}} ={t}_{\mathrm{9}} \\$$$$\\$$$$\\$$
Commented by prakash jain last updated on 24/Nov/15
$$\mathrm{This}\:\mathrm{method}\:\mathrm{is}\:\mathrm{simpler}. \\$$